Concept of Modular Design for 250 MWe PCMSR - Harto, Andang Widi (2013)
CONCEPT OF MODULAR DESIGN FOR 250 MWe PCMSR. PCMSR (Passive Compact Molten Salt Reactor) is one type of Advanced Nuclear Reactor. The PCMSR has benefit characteristics of very efficient fuel use, high safety characteristic as well as high thermodynamics efficiency. This is due to its breeding capability, inherently safe characteristic and totally passive safety system. The goal of this research is to provide a PCMSR 250 MWe design which has passive safety characteristics and conceptually can be arranged as modular reactor system. Neutronics calculation using SRAC computer code is performed to provide a passive safety characteristic core design. Heat transfer and thermodynamics calculation are performed for reactor system ans turbine system to provide these system dimension which can performed passive cooling capability of the reactor system. The calculation results show that the overall reactor system can be arranged into single reactor module with the estimated total vertical height of 22 m. The overall turbine system can be arranged into single turbine module with the estimated vertical height of 25 m. The reactor module, fuel processing system and the first stage radioactive waste treatment system are located inside the reactor building. The reactor building is equipped with passive heat dissipation system that can dissipate heat to environment for 11 days using passive heat sink pool water evaporation mechanism and ultimately using natural air circulation after the passive heat sink pool run out of water . Keywords: PCMSR, modular concept, passive heat removal system